KOLABORASI EKSEKUTIF DAN LEGISLATIF DALAM PROSES PENYUSUNAN KEBIJAKAN UMUM ANGGARAN INKLUSIF DI PROVINSI SULAWESI TENGGARA - Rahman; Muhammad Arsyad; Asriani; Muhammad Ishak Syahadat; Muhammad Amir (Journal Publicuho, 2024)
This study aims to analyze the collaboration between the executive and legislature in the formulation of inclusive budget policies in Southeast Sulawesi Province. The research method used is a qualitative approach by collecting data through interviews and analysis of related documents. The results show that close collaboration between the two institutions provides a solid foundation for inclusive and sustainable budget policymaking. Their synergy ensures alignment of development visions as well as accountability and transparency in public budget management. However, there are challenges such as lack of alignment of vision, limited transparency, and lack of effective coordination. Therefore, it is necessary to improve communication, understanding, and coordination between the two institutions to create inclusive and sustainable budget policies that have a positive impact on regional progress.